Effects of Longitudinal Glucose Exposure on Cognitive and Physical Function: Results from the Action for Health in Diabetes Movement and Memory Study. Issue 1 (27th September 2016) - Beavers, Kristen M.; Leng, Iris; Rapp, Stephen R.; Miller, Michael E.; Houston, Denise K.; Marsh, Anthony P.; Hire, Don G.; Baker, Laura D.; Bray, George A.; Blackburn, George L.; Hergenroeder, Andrea L.; Jakicic, John M.; et al.
Abstract : Objectives: To test whether average long‐term glucose exposure is associated with cognitive and physical function in middle‐aged and younger‐old adults with type 2 diabetes mellitus. Design: Prospective cohort study. Setting: Data obtained as part of the Action for Health in Diabetes (Look AHEAD) trial (NCT00017953) and Look AHEAD Movement and Memory ancillary study (NCT01410097). Participants: Overweight and obese individuals with type 2 diabetes mellitus aged 45 to 76 at baseline (N = 879). Measurements: Glycosylated hemoglobin (HbA1c) was measured at regular intervals over 7 years, and objective measures of cognitive function (Trail‐Making Test, Modified Stroop Color‐Word Test, Digit Symbol‐Coding, Rey Auditory Verbal Learning Test, Modified Mini‐Mental State Examination) and physical function (Short Physical Performance Battery, expanded Physical Performance Battery, 400‐m and 20‐m gait speed) and strength (grip and knee extensor strength) were assessed at the Year 8 or 9 follow‐up examination. Results: Average HbA1c exposure was 7.0 ± 1.1% (53 ± 11.6 mmol/mol), with 57% of participants classified as having HbA1c levels of less than 7% (<53 mmol/mol), 27% having levels of 7% to 8% (53–64 mmol/mol), and 16% having levels of greater than 8% (>64 mmol/mol). After adjustment for age, sex, race, education, smoking status, alcohol intake, knee pain, physical fitness, body mass index, diabetes mellitus medication and statin use, ancillary year visit, and study arm and site, higher HbA1c was associated with worse physical but not cognitive function. Further adjustment for prevalent diabetes mellitus–related comorbidities made all associations nonsignificant. Results did not differ when stratified according to participant baseline age (<60 vs ≥ 60). Conclusion: Results presented here suggest that, in the absence of diabetes mellitus–related complications, longitudinal glucose exposure is not associated with future cognitive and physical function. Optimal management of diabetes mellitus–related comorbidities may prevent or reduce the burden of disability associated with type 2 diabetes mellitus.